2013
DOI: 10.1103/physrevlett.110.065002
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Ionospheric Layers during Pump Frequency Stepping Near the 4th Gyroharmonic at HAARP

Abstract: We report on artificial descending plasma layers created in the ionosphere F region by high-power high-frequency (HF) radio waves from High-frequency Active Auroral Research Program at frequencies f(0) near the fourth electron gyroharmonic 4f(ce). The data come from concurrent measurements of the secondary escaping radiation from the HF-pumped ionosphere, also known as stimulated electromagnetic emission, reflected probing signals at f(0), and plasma line radar echoes. The artificial layers appeared only for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 22 publications
4
50
0
1
Order By: Relevance
“…By the same token, in the daytime/ twilight experiments Sergeev et al, 2013] DL started well before striations could develop. However, the DL in Sergeev et al's [2013] experiments were observed only for f 0 > 4f ce , consistent with Gustavsson et al's [2006] observations of stronger 427.8 nm emissions at f 0 > 4f ce . Thus, the DL formation has been explained in terms of an ionizing wavefront created by the SLT-accelerated electrons [Mishin and Pedersen, 2011;Eliasson et al, 2012.…”
Section: Uh/eb Waves Can Be Excited Via Decay Pd Omentioning
confidence: 87%
See 2 more Smart Citations
“…By the same token, in the daytime/ twilight experiments Sergeev et al, 2013] DL started well before striations could develop. However, the DL in Sergeev et al's [2013] experiments were observed only for f 0 > 4f ce , consistent with Gustavsson et al's [2006] observations of stronger 427.8 nm emissions at f 0 > 4f ce . Thus, the DL formation has been explained in terms of an ionizing wavefront created by the SLT-accelerated electrons [Mishin and Pedersen, 2011;Eliasson et al, 2012.…”
Section: Uh/eb Waves Can Be Excited Via Decay Pd Omentioning
confidence: 87%
“…First, the OTSI UH Lo [Kuo et al, 1997] of the primary UH waves with the r.m.s. This helps to explain the emergence of DL [Sergeev et al, 2013], faster descent speeds in Figure 6, and intensification of 427.8 nm emissions [Gustavsson et al, 2006] These are transferred into long scales via parametric interactions, e.g., induced scattering on ions.…”
Section: Langmuir Turbulence In the Uh Layermentioning
confidence: 97%
See 1 more Smart Citation
“…Например, в экспериментах на нагревном стенде HAARP при воздействии на ионосферу мощных радиоволн на частотах, близких к 4-й гармонике электронной циклотронной частоты f ce , обнаружено и исследовано образование слоя искусственной ионизации, опускающегося на 5-30 км от уровня отражения волны накачки до высот локального двойного резонанса [9,10]. На том же стенде, по наблюдениям искусственного радиоизлучения ионосферы (ИРИ) при нагреве на частотах возле третьей и четвертой гармоник электронной гирочастоты исследованы спектры ИРИ, возбуждаемые в диапазоне ионных акустических волн и около гармоник ионной гирочастоты [11].…”
Section: Introductionunclassified
“…The simulation results reproduce the salient observational features of ionization fronts descending from about 230 km to 150 km in a few minutes. While the simulation studies of Eliasson et al (2012) was carried out for vertical incidence of the electromagnetic wave, the experiments (Pedersen et al 2010;Mishin and Pedersen, 2011;Sergeev et al 2013) were conducted with the HF radio beam centered at the magnetic zenith, which is 14.5 degrees south to the vertical at HAARP. Early experiments have also shown enhanced electron heating and incoherent radar backscatter near MZ (e.g., Kosch et al 2000;Pedersen et al 2003;Rietveld et al 2003).…”
Section: Introductionmentioning
confidence: 99%